KINERJA PERTUMBUHAN DAN SINTASAN BENIH IKAN BAUNG (Hemibagrus nemurus) YANG DIBERI PROBIOTIK BERBEDA - saputra, Adang; mumpuni, fia sri; setiadi, eri; setiawan, irwan dwi (JURNAL MINA SAINS, 2019)
Catfish (Hemibagrus nemurus) is a local fish which has a potential for culture, but the most high mortality occurres in larval stage. The water quality is one factor that causes high mortality. The purpose of this experiment is to evaluate the optimal growth and survival performances of catfish culture with probiotic application that containing Pseudomonas sp. and Bacillus sp. Fish test in this experiment was catfish with 21 of ages, 0.11±0.03g in body weight and 2.04±0.30 cm in total length. Experimental design used complete randomize design consisted of three treatments and three replications for each treatment. The treatments were probiotic utility that containing i.e. A) without adding bacteria (control), B) adding Pseudomonas sp, and C) adding Bacillus sp. Fish culture was 60 days with feeding frequently three times a day (08:00; 14:00; and 20:00). Test paramaters were survival, length growth and weight growth, feeding conversion ratio, blood glucose, and water quality. The result of this experiment showed that the catfish with adding probiotic containing Pseudomonas sp can increase in survival (82.1%), accelerate the length growth (6.08 cm) and weight absolute growth (4.24g). Feed efficiency was 1.42, no fish stress, and improved of water quality. Key words: catfish fry, probiotic, growth, survival